Doctor Who the visual dictionary - Loborik, Jason; Corry, Neil; Rayner, Jacqueline; Darling, Andrew 1974-; Dougherty, Kerrie; John, David 1966-; Beecroft, Simon (New York, New York DK, 2014)
Presents an introduction to the popular science fiction television program, discussing its characters, plot lines, villains, gadgets, monsters, aliens, weaponry, and spaceships.
Includes index.
"Updated and expanded."
Php 395.00
Donated: Gorriceta-Rojo Family 07.29.20